Moderasi Beragama dalam Prespektif Al-Qur’an dan Hadis - Nur Aslamiyah; Siswi Tri Amalia; Ayu Annisah; Ibnati Mawaddah; Ahmad Darlis (Fakultas Tarbiyah IAI Nasional Laa Roiba, 2023)
Religious moderation is an attempt in the middle form of various existing religions. Moderation which is the middle of a group that does not really choose right or left. Islamic religious moderation is an effort in the formation of all groups in the Islamic religion which is dotted in the middle or Al-Wasth. This article refers to the Qur'an and Hadith which are the holy books of Muslims which serve as guidelines for Muslims in their daily lives. In this study, we as writers used the library research method. This is a research that collects data by retrieving data from book and journal sources. From the articles that have been presented or explained that the Al-Qur'an and Hadith do not make Muslims to do excessive or excessive extreme violence and to respect one another. Keywords: Moderation, Religion, People